2014
DOI: 10.2466/22.24.pms.119c28z8
|View full text |Cite
|
Sign up to set email alerts
|

Children's Construction Task Performance and Spatial Ability: Controlling Task Complexity and Predicting Mathematics Performance

Abstract: Summary -This paper presents a methodology to control construction task complexity and examined the relationships between construction performance and spatial and mathematical abilities in children. The study included three groups of children ( N=96); aged 7-8, 10-11 and 13-14 years. Each group constructed seven pre-specified objects.The study replicated and extended previous findings that indicated that the degree of component symmetry and variety, and the number of components for each object and available fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
5
25
0
Order By: Relevance
“…Thereby, the time was measured from start to completion of the airplane. The correlation between the ability to assemble LEGO bricks and intelligence was demonstrated by Richardson, Hunt and Richardson [12]. The retest enabled us to measure how well the work steps had been memorised and, thus, revealed memory performance.…”
Section: Methods Of Testingmentioning
confidence: 95%
“…Thereby, the time was measured from start to completion of the airplane. The correlation between the ability to assemble LEGO bricks and intelligence was demonstrated by Richardson, Hunt and Richardson [12]. The retest enabled us to measure how well the work steps had been memorised and, thus, revealed memory performance.…”
Section: Methods Of Testingmentioning
confidence: 95%
“…Thereby, the time was measured from start to completion of the airplane. The correlation between the ability to assemble LEGO bricks and intelligence was demonstrated by Richardson, Hunt and Richardson (M. Richardson, Hunt, & C. Richardson, 2014). The retest enabled us to measure how well the work steps had been memorised and, thus, revealed memory performance.…”
Section: Methods Of Testingmentioning
confidence: 99%
“…They tested spatial skills by asking participants to guess what shape would be made if paper was folded in a certain way. While they found that construction play was related to math skills through spatial skills, verbal shortterm memory was not involved [5]. We thought it was more important to test visuospatial memory with construction play, because to build Lego models you need to see and place the bricks in the correct positions.…”
Section: Box 1 | Different Types Of Memorymentioning
confidence: 97%
“…An example of instructions for Lego construction is shown in Figure 1. Example of instructions for building Lego models [5].…”
Section: How We Did the Studymentioning
confidence: 99%